(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: As people age, the prevalence of hypertension significantly rises. There is little data on the prevalence of hypertension and its contributing variables among the hospitalized elderly Bangladeshis, particularly in tertiary care settings. the purpose of the study was aimed to investigate the burden of hypertension and contributing causes in older persons admitted to a Bangladeshi teaching hospital for tertiary care. Materials and methods: This was a descriptive cross sectional study conducted during the period from July 2022 to June 2023. The study included 150 in patients who were admitted and at least 60 years old. Using an organized case record form, information was gathered through interviews, medical records, and examinations of demographic, socioeconomic, lifestyle, family history, comorbidity, anti-hypertensive drug use and blood pressure management data.Separate bivariate and multivariate logistic regression analyses were conducted to identify the factors associated with hypertension and results were expressed as Odds Ratios (ORs) with 95% CI. Results: The mean age of the patients was 64.6 ±4.6 years. Overall, prevalence of hypertension was 47.3% (41.3% old cases and 6% newly diagnosed) among them 45 (63.3%) were male. Out of 62 known hypertensive, majority (95.2%) was not taking their anti-hypertensive drugs regularly and optimal blood pressure was not achieved in 64.5% of them. Factors including being of male (OR:2.839, 95% CI:1.053, 7.654) no formal education (OR:2.217, 95% CI:1.059, 4.64) being obese by BMI criteria (OR:3.904,95% CI: 1.565, 9.559) and having a family history of hypertension (OR:8.297, 95% CI: 1.841, 17.162) were found to be significantly associated with hypertension. Conclusion: To sum up, about 50% of the elderly patients hospitalized in the medicine wards of a tertiary-level hospital had hypertension, which necessitates immediate steps to address this issue. JCMCTA 2025 ; 36 (2) : 71-76